Limited usefulness of initial blood cultures in community acquired pneumonia. Issue 4 (18th June 2004) - Corbo, J; Friedman, B; Bijur, P; Gallagher, E J
Abstract : Objective: The incidence of community acquired pneumonia (CAP) is about 4 million cases per year, with a hospitalisation rate of 20%. In non-immunocompromised patients hospitalised for CAP the rate of bacteraemia is less than 7% with predictable pathogens. Despite this, guidelines still recommend use of blood cultures (BCs) to direct treatment. This study tested the primary hypothesis that the proportion of false positive BCs would exceed the proportion of true positives. A secondary aim was to quantify the frequency with which antibiotic therapy was changed based on BC results. Method: Consecutive adults hospitalised from an urban emergency department (ED) with CAP between January 1999 and March 2001 were assessed retrospectively for study eligibility. Those with an infiltrate consistent with pneumonia on the admission chest radiograph and at least one set of BCs taken in the ED before antibiotics were given were entered into the study. Patients hospitalised within the previous two weeks, nursing home residents, and immunosuppressed patients were excluded. Results: 821 patients were admitted for CAP and 355 met inclusion criteria. The proportion of false positive BCs (10%) exceeded the proportion of true positives (9%), by 1% (95%CI −3.3% to 5.5%). Antibiotic therapy was changed on the basis of BC results in 5% of patients (95%CI 3% to 8%). Conclusion: The rate of false positive BCs in patients hospitalised with CAP is similar to the rate of true positives. BCs only infrequently lead to changes in antibiotic therapy, and in no instance were therapeutic changes driven by detection of resistant organisms. The results question the utility of routine BCs in immunocompetent patients with CAP.